Design and evaluation of biological activities of 1,3-oxazolidinone derivatives bearing amide, sulfonamide, and thiourea moieties - KAYMAKÇIOĞLU, BEDİA (WILEY-V C H VERLAG GMBH, 2018)
1,3-Oxazolidine-2-one is an important heterocyclic ring participating in the chemical structure of many drugs. In this research, 22 new amide/sulfonamide/thiourea derivatives (1-22) were obtained by the reaction of (S)-4-(4-aminobenzyl)-2(1H)-1,3-oxazolidinone with 4-substituted benzoyl chlorides, 4-substituted benzene sulfonyl chlorides, and 4-substituted phenyl isothiocyanates. The structures of all synthesized compounds were clarified by FT-IR, NMR, and mass spectroscopic and elemental analysis techniques. The synthesized compounds were screened for their antimicrobial activity. Antimicrobial susceptibility and cellular physiology were evaluated using the microbroth dilution assay and the flow cytometry method. As a result, it was determined that compound 16 displayed better antimicrobial activity than chloramphenicol against Gram-positive bacteria, especially Staphylococcus aureus. In order to understand the mechanism of effect of the compounds on the cell membrane, fluorescence microscopy was used. Cell membrane damage of the Gram positive bacteria treated with compound 16 was observed as a result of intense staining with propidium iodide. In addition, genotoxicity, cytotoxicity, and absorption, distribution, metabolism, and excretion (ADME) parameters of compound 16 were examined and it was found as non-mutagenic and non-cytotoxic at the concentration at which it showed antimicrobial activity. According to the calculated ADME parameters and drug likeness scores, the compounds can be good drug candidates, especially compound 16.
Keywords: 1,3-oxazolidine-2-one; antimicrobial activity; flow cytometry; sulfonamide; thiourea; HYDRAZONE DERIVATIVES; INHIBITORY-ACTIVITY; ANTICANCER AGENTS; OXAZOLIDINONE; RESISTANCE; TUBERCULOSIS; KLEBSIELLA; MOLECULES; MECHANISM; BACTERIA